2022
DOI: 10.1021/acs.analchem.1c04328
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption and Ionization Time-of-Flight Mass Spectrometry Analysis for the Direct Detection of SARS-CoV-2 in Nasopharyngeal Swabs

Abstract: The most common diagnostic method used for coronavirus disease-2019 (COVID-19) is real-time reverse transcription polymerase chain reaction (PCR). However, it requires complex and labor-intensive procedures and involves excessive positive results derived from viral debris. We developed a method for the direct detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in nasopharyngeal swabs, which uses matrix-assisted laser desorption and ionization time-of-flight mass spectrometry (MALDI-ToF MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
(58 reference statements)
2
21
0
Order By: Relevance
“… 16 Antibody-based affinity, ultrahigh-speed centrifugation, and ultrafiltration methods have been proposed to enrich viral materials. 17 The sulfate ester column-based enrichment method we present in this study has several advantages. Compared with other enrichment methods, our column-based method only requires sample loading, washing, and elution, which can be done feasibly without intensive personnel training.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 16 Antibody-based affinity, ultrahigh-speed centrifugation, and ultrafiltration methods have been proposed to enrich viral materials. 17 The sulfate ester column-based enrichment method we present in this study has several advantages. Compared with other enrichment methods, our column-based method only requires sample loading, washing, and elution, which can be done feasibly without intensive personnel training.…”
Section: Resultsmentioning
confidence: 99%
“…Yoshinari et al made a substantial improvement and reported an approach for the direct detection of SARS-CoV-2 in human nasopharyngeal swabs using a virus purification workflow based on filtration and anion exchange chromatography. 17 In this workflow, nonviral proteins were removed by molecular weight cutoff ultrafiltration (MWCO). The virus was lysed with 2-propanol and the anionic nucleocapsid protein (N protein) was preferentially adsorbed on positively charged Sepharose XL.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations